The Influence of environmental factors on small pelagic target species (Sardine, Anchovy, and Mackerel) in the southern Alboran Sea (Western Mediterranean). - Jghab, Ayman (UMA Editorial, 2024)
Small pelagic fishing is the main fishing activity in the Moroccan Mediterranean Sea. While the decline in these small pelagic fisheries is thought to be primarily due to fishing, climate change and its impact on the disruption of the marine ecosystem may also have affected these species, especially since the Mediterranean Sea is a semi-enclosed and highly sensitive to environmental changes. Linear model analysis reflects the possible effects of warming in the Alboran Sea and reduced AJ kinetic energy on the observed trend of decreasing sardine landings. Chlorophyll concentrations in surface waters appear to be an important factor regulating the variability in annual sardine landings. Finally, for long-term and inter-annual variation, the linear model was able to explain approximately 60% of the variance in landing. As for the possible effects of environmental changes on Atlantic chub mackerel. Our results suggest that this specie may be more sensitive to salinity, temperature, ocean current and wind patterns, and anchovy (prey) abundance, and that the changes in these variables may affect their abundance and ultimately fishing exploitation. On the other hand, the increase of temperature and salinity could favorite the expansion of this specie on behalf of other small pelagic species (Anchovy, and Sardine). These results demonstrate the need to consider the impact of oceanographic processes when managing fishery resources and suggest that the dynamics of these pelagic fish populations in the Alboran Sea are significantly influenced by the inflowing Atlantic currents.
Keywords: Evaluación del impacto ambiental - Tesis doctorales; Alborán - Aspectos ambientales; Cambios climáticos; Alboran Sea; Climate change; Small pelagic fish; Sardine; Modelling